BIOIMPEDANCE-BASED DIAGNOSTICS IN CLINICAL PRACTICE - Yorqin Sattarov; Rukhshona Turayeva (Modern American Journals, 2025)
Bioimpedance-based diagnostics have emerged as a non-invasive, rapid, and reliable method for assessing various physiological and pathological conditions in clinical practice. By measuring the electrical impedance of biological tissues, this technique provides valuable information about tissue composition, fluid status, and cellular health. Its applications span cardiovascular monitoring, cancer detection, body composition analysis, and evaluation of edema or dehydration. The bioimpedance method offers advantages such as safety, portability, and cost-effectiveness, making it suitable for bedside and ambulatory settings. Recent advances in instrumentation and signal processing have enhanced measurement accuracy and diagnostic capability. Despite certain limitations related to standardization and interpretation, bioimpedance diagnostics continue to grow as a complementary tool alongside traditional imaging and laboratory tests. This resume highlights the principles, clinical applications, benefits, and challenges of bioimpedance-based diagnostics, emphasizing its potential to improve patient management and personalized healthcare.
Keywords: Bioimpedance, bioelectrical impedance analysis, non-invasive diagnostics, tissue impedance, clinical applications, fluid status monitoring, body composition, edema detection, cancer diagnostics, cardiovascular monitoring, personalized medicine, biomedical instrumentation.